2009
DOI: 10.1007/s00723-009-0101-8
|View full text |Cite
|
Sign up to set email alerts
|

The Electronic State of Flavoproteins: Investigations with Proton Electron–Nuclear Double Resonance

Abstract: Electron–nuclear double resonance (ENDOR) spectroscopy provides useful information on hyperfine interactions between nuclear magnetic moments and the magnetic moment of an unpaired electron spin. Because the hyperfine coupling constant reacts quite sensitively to polarity changes in the direct vicinity of the nucleus under consideration, ENDOR spectroscopy can be favorably used for the detection of subtle protein–cofactor interactions. A number of pulsed ENDOR studies on flavoproteins have been published durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
45
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 50 publications
7
45
1
Order By: Relevance
“…Following previously reported literature values for the experimental parameters, the static magnetic field, oscillating frequency, and amplitude were specifically chosen to ensure the most probable success for eliciting a magnetic field response. Many biological molecules exhibit hyperfine splitting constants that range from 0.1–35 MHz [36], [38], and therefore, we propose that 7 MHz frequency most likely influence cellular chemical reactions that involve biomolecules with hyperfine couplings of equal energies [36], [37]. To fully separate the contributions from Zeeman and hyperfine couplings, the magnetic field, frequency, and intensity dependence needs to be evaluated, of which is beyond the scope of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Following previously reported literature values for the experimental parameters, the static magnetic field, oscillating frequency, and amplitude were specifically chosen to ensure the most probable success for eliciting a magnetic field response. Many biological molecules exhibit hyperfine splitting constants that range from 0.1–35 MHz [36], [38], and therefore, we propose that 7 MHz frequency most likely influence cellular chemical reactions that involve biomolecules with hyperfine couplings of equal energies [36], [37]. To fully separate the contributions from Zeeman and hyperfine couplings, the magnetic field, frequency, and intensity dependence needs to be evaluated, of which is beyond the scope of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…due to substrate binding, altered geometries of hydrogen bonds, surrounding amino acids have been shown experimentally535455565758596061 and theoretically436263. If such inherent heterogeneities existed, they could potentially lead to significantly larger levels of variation than the 2% level assumed here.…”
mentioning
confidence: 69%
“…isoalloxazine moiety) of a flavin cofactor radical of flavoproteins, including cryptochromes61, is highly sensitive to change in the protein environment. This has allowed hyperfine spectroscopy methods to use flavin cofactor radicals as a spin probe5960616263. Particularly, electron nuclear double resonance (ENDOR) studies of flavoproteins have shown changes of proton hyperfine couplings of the flavin’s isoalloxazine moiety upon substrate binding535456.…”
Section: Methodsmentioning
confidence: 99%
“…Qualitatively, the hfcs from Rf-LumP are comparable to those obtained from other flavoproteins. 79 Upon closer inspection, the A iso values of the protons H(1′) and H(8α) are more related to those obtained in flavodoxins than in photolyases and other flavoproteins. 79 This finding can be rationalized in terms of a different flavin-binding situation.…”
Section: ■ Discussionmentioning
confidence: 89%
“…79 Upon closer inspection, the A iso values of the protons H(1′) and H(8α) are more related to those obtained in flavodoxins than in photolyases and other flavoproteins. 79 This finding can be rationalized in terms of a different flavin-binding situation. Whereas the flavin cofactor is deeply buried in, e.g., photolyases, it is located near the surface of the protein in flavodoxins, with the xylene ring protruding into the solvent.…”
Section: ■ Discussionmentioning
confidence: 89%